Thermal fatigue of laser modified tool steels mould surface at high temperature - Annie, Lau Sheng (2020)
In die casting environment, tool steel service life decrease due to the oxidation, erosion, corrosion and thermal fatigue cracks which occur on the die surface that cause production downtime and losses. Thermal fatigue cracks is a significant failure which is around 70% in die casting dies. In order to reduce the thermal fatigue cracks, the surface roughness (SR) and hardness of laser modified samples have to be tailored. In this study, the effect of laser surface modification parameters on SR and hardness was investigated to reduce the thermal fatigue crack. The hardness and microstructure of laser modified and asreceived AISI H13 tool steels that subjected to the thermal fatigue test were also investigated. First, a full factorial design of experiment (DOE) was developed. The three factors were peak power (W), pulse repetition frequency (PRF) and overlap rate (%) with the range of 1500-1900W, 40-60Hz and 10-30% respectively. Then, fiber laser system with pulse mode was applied on the surface of AISI H13 tool steel. The SR and hardness of all the laser modified samples were then measured. After that, the as-received AISI H13 and selected laser modified samples were used to conduct a thermal fatigue test which involve cyclic immersion test. The thermal fatigue test was conducted by continuously heating the samples in molten aluminium and cooling in a water bath at a respective temperature range of 850-900 °C and 27 °C. The characterisation of asreceived and laser modified samples for hardness, microstructure and thermal fatigue crack conducted before and after 5000 cycles. From the findings, the hardness of the laser modified samples increased 3 times from 203.3 HV to 744.6 HV. However, the SR has also increased from 1.3 µm to the range of 8.97-42.31 µm due to the various parameters of laser surface modification. The overlap rate has a significant effect on hardness. While, a low SR can be obtained at 1900 W of peak power and 10% of overlap rate. However, the PRF was an insignificant parameter to affect the hardness and SR. Prediction model was developed to identify suitable laser parameters setting for the intended value of SR and hardness. The hardness and microstructure of laser modified samples before and after thermal fatigue (TF) test were investigated. The hardness of laser modified samples decreased dramatically due to the microstructure changed. However, the laser modified samples significantly performance well than the as-received AISI H13. Laser modified samples reduce the number and length of cracks from 27 to 17 and 6.87 mm to 1.84 mm respectively. In conclusion, a suitable laser parameters setting can produce a low SR and high hardness sample. The thermal fatigue test proved that high hardness has a high resistance of thermal fatigue which can reduce the thermal fatigue cracks. Low SR can also reduce the accumulation of oxide which can generate the thermal fatigue cracks. Overall, this study is significant to enhance the surface properties such as resistance of thermal fatigue and hardness for AISI H13 tool steel in high temperature applications.